mylecture6 - EE264: Lecture 6 IIR Filters cont....

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: EE264: Lecture 6 IIR Filters cont. Differential equation to Difference equation Transformation When a system has a transfer function H ( s ) of rational form, the system relates its output to its input through a Linear Constant Coefficient Differential Equation. Approximating derivatives with (discrete-time) differ- ences allows us to translate the differential equation to a difference equation that defines a Discrete-time system which will approximate the differential equation if the sampling period is small enough. Example: Let x ( t ) and y ( t ) be the input and output of a continuous-time system with the following transfer function: H c ( s ) = s- 1 ( s + 1)( s + 2) = s- 1 s 2 + 3 s + 2 then Y ( s ) X ( s ) = s- 1 s 2 + 3 s + 2 Y ( s )( s 2 + 3 s + 2) = X ( s )( s- 1) d 2 y ( t ) dt 2 + 3 dy ( t ) dt + 2 y ( t ) = dx ( t ) dt- x ( t ) Let x [ n ] = x ( nT ) , we can approximate derivatives at times nT as follows: dx ( t ) dt vextendsingle vextendsingle vextendsingle vextendsingle t = nT ≈ x [ n + 1]- x [ n ] T forward difference dx ( t ) dt vextendsingle vextendsingle vextendsingle vextendsingle t = nT ≈ x [ n ]- x [ n- 1] T backward difference dx ( t ) dt vextendsingle vextendsingle vextendsingle vextendsingle t = nT ≈ x [ n + 1]- x [ n- 1] 2 T symmetrical difference d 2 x ( t ) dt 2 vextendsingle vextendsingle vextendsingle vextendsingle vextendsingle t = nT ≈ x [ n +1]- x [ n ] T- x [ n ]- x [ n- 1] T T = x [ n + 1]- 2 x [ n ] + x [ n- 1] T 2 Using the forward difference approximation we obtain: y [ n + 1]- 2 y [ n ] + y [ n- 1] T 2 + 3 y [ n + 1]- y [ n ] T + 2 y [ n ] = x [ n + 1]- x [ n ] T- x [ n ] Taking the z-transform on both sides of the difference equation we get: H ( z ) = Y ( z ) X ( z ) = 1 T- ( 1 T + 1) z- 1 ( 1 T 2 + 3 T )- ( 2 T 2 + 3 T- 2) z- 1 + 1 T 2 z- 2 Copyright c circlecopyrt 1995–1996 by G. Plett. Copyright c circlecopyrt 1998–2004 by M. Kamenetsky. Copyright c circlecopyrt 2005 by A. Flores 65 66 IIR Filters cont. Lect. 6 Bilinear (but not linear) Transformation To avoid aliasing, we need a one-to-one mapping from the s-plane to the z-plane. Consider s = 2 T parenleftBigg 1- z- 1 1 + z- 1 parenrightBigg ⇒ H ( z ) = H c parenleftBigg 2(1- z- 1 ) T (1 + z- 1 ) parenrightBigg which defines a bilinear transformation z = 1 + T 2 s 1- T 2 s ⇔ s = 2(1- z- 1 ) T (1 + z- 1 ) Q: Is this a legal transformation? A: Let s = j Ω . Then z = 1 + j Ω T 2 1- j Ω T 2 = radicalBig 1 + Ω 2 T 2 4 negationslash tan- 1 parenleftBig Ω T 2 parenrightBig radicalBig 1 + Ω 2 T 2 4 negationslash tan- 1 parenleftBig- Ω T 2 parenrightBig = 1 negationslash 2 tan- 1 parenleftbigg Ω T 2 parenrightbigg So, | z | = 1 . Also, if σ < , | z | < 1 , so OK....
View Full Document

This note was uploaded on 10/24/2009 for the course SCE sysc5602 taught by Professor El-tanany during the Winter '09 term at Carleton CA.

Page1 / 9

mylecture6 - EE264: Lecture 6 IIR Filters cont....

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online